Profile of Deaths Due to Poisoning: Autopsied at Ssims & Rc - A Cross Sectional Study - Anand Patil1, Rakesh M Marigoudar2, Vijayakumar B. Jatti3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Poisoning is an important health problem in every country of the world and it is a known fact that the incidence of poisoning in India is highest and it is estimated that more than 50,000 people die every year from poisoning1. Poisoning affects all age groups from infants to seniors, but poisoning in teens and adults are more serious and it contributes to morbidity and mortality. Due to easy accessibility of poisons and lack of awareness, self-poisoning deaths are more common. In most of the poisoning deaths, the poison consumed was unknown at the time of autopsy but Forensic Science Laboratory plays a vital role in detection of poison. With this background, the present study has been carried out to determine the profile of poisoning cases, autopsied at SSIMS&RC, DAVANGERE, KARNATAKA. The study revealed that more number of poisoning is seen in males (62.3%) as compare to females (37.7%). Common age group affected is 21 to 30 years, followed by 31 to 40 years and least in 41 to 50 years. Agriculture group is commonly affected, followed by unemployed and least in government employees. Majority of victims belongs to lower socioeconomic group (84%). The suicidal deaths by poisoning (97%) being highest followed by homicidal and accidental.